2020
DOI: 10.1590/1678-4685-gmb-2019-0068
|View full text |Cite
|
Sign up to set email alerts
|

Intense proliferation of rDNA sites and heterochromatic bands in two distantly related Cuscuta species (Convolvulaceae) with very large genomes and symmetric karyotypes

Abstract: The genome size varies widely among angiosperms but only a few clades present huge variation at a low phylogenetic level. Among diploid species of the genus Cuscuta the genome size increased enormously in at least two independent lineages: in species of subgenus Monogynella and in at least one species (C. indecora) of the subgenus Grammica. Curiously, the independent events lead to similar karyotypes, with 2n = 30 mostly metacentric chromosomes. In this paper we compared the patterns of heterochromatic bands a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
14
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 9 publications
(16 citation statements)
references
References 54 publications
1
14
1
Order By: Relevance
“…The latter studies revealed a numerical variation of these bands, with species having few bands, like C. denticulata Engelm. with only one pair of evident CMA + /DAPIbands, to species like C. monogyna Vahl, with approximately 90 CMA + /DAPIbands and DAPI + /CMAbands in pachytene (Ibiapino et al, 2019(Ibiapino et al, , 2020. Despite this variation, our previous unpublished data showed that karyotypes with less bands are more frequent, even in polyploid species.…”
Section: Discussionmentioning
confidence: 80%
See 4 more Smart Citations
“…The latter studies revealed a numerical variation of these bands, with species having few bands, like C. denticulata Engelm. with only one pair of evident CMA + /DAPIbands, to species like C. monogyna Vahl, with approximately 90 CMA + /DAPIbands and DAPI + /CMAbands in pachytene (Ibiapino et al, 2019(Ibiapino et al, , 2020. Despite this variation, our previous unpublished data showed that karyotypes with less bands are more frequent, even in polyploid species.…”
Section: Discussionmentioning
confidence: 80%
“…In the species with a higher number of CMA + /DAPI - or DAPI + /CMA - bands, they are localised in interstitial regions. There is no evidence that this banding pattern is different for each subgenus and there may be similar patterns between different subgenera (Ibiapino et al ., 2020). In the three species of the subgenus Pachystigma analysed here, the multiple CMA/DAPI bands were mainly present at the largest pairs.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations